Patient-doctor relationships: an alliance in health care - Pereira, Ana Cristina (2013)
Introduction: The reasons that lead patients to seek health care, the value of symptoms, and their perception of problems depend on the personal history, cultural, socioeconomic and family context of the patient. Illness (the disease experience of the patient) and disease (the medical disease) are terms used to describe what the patient feels when he goes to the doctor and what he has when he returns home after the consultation. This case aims to highlight the importance of the presenting complaint and its exploration by the Family Physician. Case Description: A 56 year-old unemployed man came to his first consultation in four years because of a lesion on his forearm, which has been present for five years. He was not receiving medication, did not smoke, and had moderate alcohol consumption. There was one visit recorded in 2007 with a diagnosis of hypertension. The blood pressure at the current visit was found to be elevated. In addition, a vegetative tumor was noted on his forearm. The patient agreed to renew follow-up, to perform the necessary tests, and accepted a referral to the dermatology clinic. A squamous cell carcinoma was diagnosed. The patient returned to clinic to obtain the results of his tests. A diagnosis of diabetes mellitus was suspected and confirmed. His blood pressure remained elevated and medication was prescribed. Comment: The family physician must try to understand why patients choose to consult or delay consultation. Is there a fear of being labeled as a sick person? Is the social network weak? This patient, who considered himself healthy, was labeled with a different disease at each visit. The family physician should manage expectations, explore them, discuss them and negotiate with the patient so that care is more effective and better accepted by patients. This can have implications for adherence to treatment and patient satisfaction with the consultation.